Prognostic value of subclinical congestion assessed by lung ultrasound in STEMI patients in a short-term follow-up. (3rd May 2023) - Rodriguez-Gonzalez, C; Ribas-Barquet, N; Rivas-Lasarte, M; Simon-Ramon, C; Vidal-Burdeus, M; Rodriguez-Sotelo, L; Sionis, A; Giralt-Borrell, T; Izquierdo-Marquisa, A; Farre, N; Vaquerizo-Montilla, B; Carreras-Mora, J
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): This project received a Scholarship for Training and Research from the Association of Ischemic Heart Disease and Cardiological Critical Care of the Spanish Society of Cardiology and an Original Research Projects Grant from the Catalan Society of Cardiology. Background: Heart failure (HF) is an important prognostic factor in ST-segment elevation myocardial infarction (STEMI). Although most STEMI patients are Killip-Kimball class I (KK-I) at admission, there is a risk of developing HF during hospitalization and follow-up. Lung ultrasound (LUS) is an easy, fast, and accurate technique that allows pulmonary congestion to be diagnosed even in pre-clinical stages. Several risk scores have been developed to identify low-risk STEMI patients, nonetheless any of these scores include LUS assessment. Purpose: We evaluated the prognostic value of subclinical congestion assessed by LUS at hospital admission in patients with KK-I STEMI. Primary endpoint was a composite of readmission for HF or new acute coronary syndrome or death during 30-day follow-up. Methods: This was a multicenter study prospectively enrolling 300 patients admitted for KK-I STEMI. LUS was performed during the first 24 hours after revascularization by and independent operator and B-lines were counted off-line differentiating between patients with wet lung (≥ 3 B-lines in at least one lung field) or dry lung. To assess whether LUS could improve the predictive capacity of current risk scales, a model with categorical result of LUS (dry/wet lung) and categorical result of Zwolle score (low/higher risk) was compared to the isolated result of Zwolle score and net reclassification index (NRI) was calculated. Results: Wet lung patients had a higher risk of developing the follow-up composite endpoint (hazard ratio [HR] 10.8, 95% CI 2.6-45.2, p=0.001). After adjusting by a propensity score including age, sex, hypertension, chronic kidney disease (glomerular filtration rate <60ml/min/1, 73m2), previous atrial fibrillation/flutter, anterior STEMI, and LVEF, a LUS finding of wet lung remained an independent risk factor for the composite endpoint (adjusted HR 5.4, 95% CI 1.0-28.7, p=0.049). LUS was able to predict de composite endpoint with 62.5% sensitivity, 86.8% specificity, 11.1% positive predictive value and 98.9% negative predictive value. LUS improved the predictive capacity of the Zwolle score (net reclassification improvement = 0.99, 95% CI 0.29-1.69, p=0.006) to predict the composite endpoint. CONCLUSIONS: Early subclinical pulmonary congestion identified by LUS in KK-I STEMI patients at hospital admission is a strong predictor of adverse outcomes at 30-day follow-up. Patients without subclinical congestion have a very low risk of adverse outcomes and can potentially benefit from an early discharge. LUS improves the predictive ability of the Zwolle risk score, allowing a more accurate identification of low-risk patients.